Effects of sodium-glucose cotransporter-2 inhibitors on nutritional status in heart failure with reduced ejection fraction - Arslan,Kadem (2022)
SUMMARY OBJECTIVE: This study aimed to evaluate the effects of sodium-glucose cotransporter-2 inhibitors on nutritional status in patients with heart failure with reduced ejection fraction. METHODS: The sodium-glucose cotransporter-2 inhibitor treatment was initiated in 153 patients with heart failure with reduced ejection fraction who were symptomatic despite optimal medical treatment and were followed up for 6 months. The Minnesota Living With Heart Failure Questionnaire scores, New York Heart Association functional class, NT-pro-BNP levels, and nutritional index scores of the patients were evaluated before sodium-glucose cotransporter-2 inhibitor treatment and at the 6-month follow-up. The nutritional status of the patients was evaluated with the COntrolling NUTritional Status score, Geriatric Nutritional Risk Index, and Prognostic Nutritional Index. RESULTS: After sodium-glucose cotransporter-2 inhibitor treatment, significant changes were observed in the mean scores of the three different nutritional indexes: COntrolling NUTritional Status (before: 2.76±2.43 vs. after: 1.12±1.23, p<0.001), Geriatric Nutritional Risk Index (before: 98.2±9.63 vs. after: 104.4±5.83, p<0.001), and Prognostic Nutritional Index (before: 37.9±4.63 vs. after: 42.9±3.83, p<0.001) scores. A significant decrease in the number of patients with malnutrition was observed according to the COntrolling NUTritional Status (before: 46.4% vs. after: 9.7%, p<0.001), Geriatric Nutritional Risk Index (before: 41.8% vs. after: 18.9%, p=0.006), and Prognostic Nutritional Index (before: 36.6% vs. after: 13.7%, p=0.007) scores. A significant functional improvement was observed in patients after sodium-glucose cotransporter-2 treatment: Minnesota Living With Heart Failure Questionnaire scores (before: 39.2±7.2 vs. after: 20.4±7.4, p<0.001), NT-pro-BNP levels (before: 2989±681 vs. after: 1236±760, p<0.001), and New York Heart Association class (before: class II-III: 95.5%; class IV: 4.5% vs. after: class II-III: 78%; class IV: 0%, p<0.001). CONCLUSION: In patients with heart failure with reduced ejection fraction who are symptomatic despite optimal medical treatment, the addition of an sodium-glucose cotransporter-2 inhibitor to treatment can significantly improve both the nutritional and functional statuses.